2019
DOI: 10.1007/s12034-018-1718-8
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of exo-cyclic aromaticity in triangular heterocyclic $$\hbox {B}_{2}\hbox {F}_{2}$$ B 2 F 2 X systems (X $$=$$ = O, S, Se, NH)

Abstract: Aromaticity is an important concept in chemistry which extends over a wide range of molecular systems and imparts unique features to the molecules possessing it. In the present work, novel heteroatomic molecular systems are proposed which demonstrate non-conventional aromaticity where the molecules accomplish the aromatic sextet and hence stabilization through the conjugation of π-electrons from exo-cyclic substituents. A considerable σ-aromaticity is also observed which does not involve the exo-cyclic atoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…High spin organic systems can be designed using Baird's rule of 4 n electron triplet aromatics [35] . Recently it is shown that delocalized (4 n +2) π electron system can also be achieved through the back donation of electrons from the group which is exo‐cyclic to the ring [36,37] . Here, the concept of this exo‐cyclic aromaticity is categorically used to stabilize high spin systems.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…High spin organic systems can be designed using Baird's rule of 4 n electron triplet aromatics [35] . Recently it is shown that delocalized (4 n +2) π electron system can also be achieved through the back donation of electrons from the group which is exo‐cyclic to the ring [36,37] . Here, the concept of this exo‐cyclic aromaticity is categorically used to stabilize high spin systems.…”
Section: Figurementioning
confidence: 99%
“…The electron dot structure of the delocalizable π electrons are given in Figure S1 (Supporting Information) and the optimized bond lengths are given in Figure 1. This type of delocalization of the electron on the p z orbital of exo‐cyclic carbon atom can help the ring to gain (4 n +2) π electrons and impose aromaticity in the systems [36,37] …”
Section: Figurementioning
confidence: 99%